Therapeutic Effect of Platelet-Rich Plasma in Rat Spinal Cord Injuries - Chen, Nan-Fu; Sung, Chun-Sung; Wen, Zhi-Hong; Chen, Chun-Hong; Feng, Chien-Wei; Hung, Han-Chun; Yang, San-Nan; Tsui, Kuan-Hao; Chen, Wu-Fu (Frontiers in Neuroscience, 2018)
Platelet-rich plasma (PRP) is prepared by centrifuging fresh blood in an anticoagulant state, and harvesting the platelet-rich portion or condensing platelets. Studies have consistently demonstrated that PRP concentrates are an abundant source of growth factors, such as platelet-derived growth factor (PDGF), transforming growth factor a (TGF-a), insulin-like growth factor 1 (IGF-1), and epithelial growth factor (EGF). The complex mechanisms underlying spinal cord injury (SCI) diminish intrinsic repair and neuronal regeneration. Several studies have suggested that growth factor-promoted axonal regeneration can occur for an extended period after injury. More importantly, the delivery of exogenous growth factors contained in PRP, such as EGF, IGF-1, and TGF-a, has neurotrophic effects on central nervous system (CNS) injuries and neurodegenerative diseases. However, only a few studies have investigated the effects of PRP on CNS injuries or neurodegenerative diseases. According to our review of relevant literature, no study has investigated the effect of intrathecal (i.t.) PRP injection into the injured spinal cord and activation of intrinsic mechanisms. In the present study, we directly injected i.t. PRP into rat spinal cords and examined the effects of PRP on normal and injured spinal cords. In rats with normal spinal cords, PRP induced microglia and astrocyte activation and PDGF-B and ICAM-1 expression. In rats with SCIs, i.t. PRP enhanced the locomotor recovery and spared white matter, promoted angiogenesis and neuronal regeneration, and modulated blood vessel size. Furthermore, a sustained treatment (a bolus of PRP followed by a 1/3 dose of initial PRP concentration) exerted more favorable therapeutic effects than a single dose of PRP. Our findings suggest by i.t. PRP stimulate angiogenesis, enhancing neuronal regeneration after SCI in rats. Although PRP induces minor inflammation in normal and injured spinal cords, it has many advantages. It is an autologous, biocompatible, nontoxic material that does not result in a major immune response. In addition, based on its safety and ease of preparation, we hypothesize that PRP is a promising therapeutic agent for SCI.